Dorms and Covid-19: Resilient Architecture Approach to Darul Ulum Islamic Boarding School Dormitory Design - Nur, Azizah Laily; Mutiara, Elok; Handryant, Aisyah Nur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 3 No 1 (2022): Proceeding of International Conference on Engineering, Technology, and Social Sciences, 2023)
Covid-19 pandemic has been going on for the past few years. One of the impacts of the pandemic is change in education sector, including in pesantren . Indonesian Doctors Association (IDI) issues requirements that must be met if a boarding school is opened. Life in a boarding school, especially in dormitory housing is identical with shared activities. The issue of the pandemic and the potential of the dormitory environment become a new cluster for the spread of Covid-19 is the background for designing resilient dormitory. The Resilient Architecture approach that is applied stems from the resilient theory by Istiadji, Hardiman, and Satwiko which has four principles, namely: Recovery, Responsive, Adaptive, and Absorptive. The principles of resilience architecture approach in the design are complemented by two Islamic principles those are protecting views and maintaining privacy. The design process uses linear analysis which applicate the resilient concept in the arrangement of mass and user circulation, natural lighting of the room, the structure and processing of the building's facade, as well as the open space on the site. The application of four principles of resilient architecture and two Islamic principles makes the dormitory design able to adapt to changes during the pandemic and the environment around the site.